ISIS’s COVID-19 Messaging on Twitter: An Analysis of Tweet Sentiment and Emotions - Lee, Claire Seungeun (Crime & delinquency, 2022)
Terrorist groups have integrated social discourse into their narratives to exploit public fear. The COVID-19 pandemic has provided an opportunity to measure how ISIS modified narratives, stimulated group communication, reinforced enemy hatred, and employed new mobilization/recruitment strategies. Using Significance Quest Theory, this study examines ISIS?s Twitter activity related to COVID-19 (N = 630,201) and how the group leverages the psychological effects and the social disruption. This study employs a two-stage analysis of tweet sentiment and emotion with a statistical analysis of retweet-motivating factors to explore how ISIS manages its narrative, needs, and network. Results show content with higher negative sentiment scores had more retweets across all sample sets. Insights include deeper understanding of extremist activity and group adaptation to external changes.